Sistem Pendukung Keputusan Peramalan Nilai Inflasi Menggunakan Metode Single Moving Average Dan Exponential Smoothing - Fathur Rohman - UBSI Jakarta; Septiana Hasanah - STMIK Nusa Mandiri (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2019)
ABSTRACT - Inflation is a problem that haunts the economy of each country. Its development which continues to increase is an obstacle to economic growth in a better direction. Inflation itself is an event that describes the situation and conditions in which the price of goods increases and the value of the currency weakens. Presentation of inflation value predictions is important to help the community make adjustments to daily expenses and also to be a reference for the government in determining policies, on this occasion the author uses a single moving average forecasting method (two-month and three-month intervals) and exponential smoothing (alpha 0 , 3; 0.5 and 0.8). The best analysis results were obtained using the exponential smoothing method with an alpha value of 0.3 because it has a smaller level of mean squared error which is 0.0513 compared to the single moving average method (two months and three months intervals) or exponential smoothing (alpha 0.5; 0.8).Keywords: Inflation, Forecasting, Single Moving Average, Exponential Smoothing. ABSTRAK - Inflasi merupakan suatu masalah yang menghantui perekonomian setiap negara. Perkembangannya yang terus-menerus mengalami peningkatan menjadi hambatan pada pertumbuhan ekonomi ke arah yang lebih baik. Inflasi itu sendiri adalah suatu kejadian yang menggambarkan situasi dan kondisi di mana harga barang mengalami kenaikan dan nilai mata uang mengalami pelemahan. Penyajian prediksi nilai inflasi menjadi penting untuk membantu masyarakat melakukan penyesuaian terhadap pengeluaran sehari-hari dan juga untuk menjadi acuan pemerintah dalam menentukan kebijakan, pada kesempatan ini penulis menggunakan metode peramalan single moving average (interval dua bulan dan tiga bulan) dan exponential smoothing (alpha 0,3 ; 0,5 dan 0,8). Hasil analisis terbaik diperoleh dengan menggunakan metode exponential smoothing dengan nilai alpha 0,3 karena memiliki tingkat mean squared error lebih kecil yaitu 0,0513 dibandingkan metode single moving average (interval dua bulan dan tiga bulan) ataupun exponential smoothing (alpha 0,5 ; 0,8).Kata Kunci: Inflasi, Forecasting, Single Moving Average, Exponential Smoothing.